Methylation and rearrangement of mouse intracisternal a particle genes in development, aging, and myeloma. - Mays-Hoopes, L L (1983)
Sequences of DNA that hybridize on Southern blots with cloned intracisternal A-particle (IAP) sequences have been examined in genomic DNAs of neonatal mice, livers of adult mice (3, 6, 12, 18, 24, and 26 months old), and the solid myeloma tumor MOPC-315. The isoschizomers HpaII (CCGG or mCCGG) and MspI (CCGG or CmCGG) were used to assess methylation. All the DNAs produced a major 0.5-kilobase MspI fragment that hybridizes with IAP probe. Only the myeloma DNA, and to a much lesser degree DNA from senescent mouse liver, produced this fragment in HpaII digest; the other DNAs all had IAP sequences resistant to HpaII digestion. These sequences thus become fully methylated to CmCGG early and remain so in adult life, except in the myeloma cells that are expressing the IAP genes. An increase in MspI-sensitive sites in IAP gene-containing DNA was observed in aging mice. The probe used to assess methylation, a 0.8-kilobase fragment produced by BamHI-HindIII double digestion, is common to several cloned IAP genes and is part of a region of DNA which is conserved in genomes of all mouse tissues. The probe hybridized to 1.5- and 1.4-kilobase doublet bands produced by BamHI, HindIII, and EcoRI triple digestions of neonatal DNA. These two bands were found in neonatal livers of Swiss Webster, BALB/c, and C57BL/6J mouse strains, showed less in adult liver, and were barely detectable in senescent livers from C57BL/6J mice.